The Utilization of Database for Administration Purposes as a Strategy Facing the New Normal: Prototype Development of e-Office - Mustofa, Fahmi Charish; Ahmad, Umar Ali; Nugroho, Bangkit Indarmawan (Kadaster: Journal of Land Information Technology, 2023)
The rise of Industry 4.0 has revolutionized work dynamics, particularly evident in the widespread adoption of remote working practices. Employees are no longer confined to traditional office spaces; instead, they have the flexibility to work efficiently from various locations. This study delves into the creation of a remote presence application, named "The SIMPEG-Pres," within the framework of an "e-Office Application." Tailored for Ministry of Agraria and Spatial Planning/National Land Agency employees, this application incorporates remote check-in features, focusing on transparency, informativeness, and georeferenced capabilities. The e-Office application requires seamless extraction of attendance data from the services layer, manifesting as a mobile application. Employing the SIMPEG-Press application in the SIMPEG e-Office system, utilizing an Oracle database and Python backend, the research validates the "published or perished" paradigm and ensures database security. The methodology involves implementing a dummy database and categorizing employee attendance and location zones based on specific parameters, guaranteeing efficient system and user management practices. The study culminates in a comprehensive matrix outlining Land Information System (LIS) development within the BPN environment, analyzed through system development theory. Additionally, the research outlines potential opportunities and challenges in the future trajectory of LIS development, providing valuable insights for both practitioners and scholars. Keywords: Application Programming Interfaces, Location Based Services, Land Information System, Remote Presence Application, Python.